Pengembangan Aplikasi SOLID-Calculator untuk Pengukuran Kualitas Desain Diagram Kelas - Intan Oktafiani; Muhammad Fauzi Arda Saputra (SAINS DAN INFORMATIKA : RESEARCH OF SCIENCE AND INFORMATIC, 2022)
Today's development of information technology makes the competition for software products increasingly tight. Developers should release immediately and gain the trust of users. One crucial strategy that needs to be done is improving the software's quality. The application of software engineering principles in every development process is how to deliver quality software. The SOLID principles are the standard for developers to build well-designed software. Using this principle will make the software easier to understand, more flexible, easy to maintain, and testable. Implementation of the SOLID Principles can be started from the design of the class diagram. In this research, a software development called SOLID-Calculator was carried out to speed up measuring the quality of class diagrams. When developers can quickly find out the level of design quality, the faster errors can be detected and corrected. It is believed that the product will soon enter the market share and even excel in user ratings.